Effect of Operating Cash Flow on Stock Return of Firms Listed In Nairobi Security Exchange - Kipngetich, Samoei Ben; Tenai, Joel; Kimwolo, Andrew (Eastern Journal of Economics and Finance, 2021)
The main aim of the paper was to establish the effect of operating cash flow on stock return of firms listed in NSE. The study was informed by Free Cash Flow (FCF) theory. Census survey was adapted to review financial statements for 29 listed non-financial firms at NSE that had consistent data for all the study variables. Secondary data was extracted for 12 years from 2007-2019 with the aid of a data collection sheet. Explanatory research design which is panel in nature was followed by this study. Both descriptive and inferential statistics were used in data analysis. Panel data regression was used to make inferences and test research hypothesis. Fixed and Random effects methods were used to analyze the balanced panel data using STATA statistical package and Hausman test established that Random effect model was the most ideal method to analyze data in this study. The findings indicated that operating cash flow positively and significantly influenced the stock returns for firms listed at NSE. The study concludes that operating cash flow information affects stock returns. Therefore, the study advocates for firms to increase their levels of operating cash flows through prudent utilization of cash resources since it enhances the stock returns.